The reception of the emotions around the violence in the mythic character of Medea, in Le cycle médéen by Pascal Quignard (El Hilo de la Fabula, 2025)
Perhaps the reasons of the mythical character of Medea’s rare persistence are based on her condition of major dramatism between the figures of the classical theatre, ambivalence of a woman and a filicidal mother. In its multiple versions, from Euripides to nowadays, this myth has gone through different genres. That is the case of the French author Pascal Quignard, who resignifies the protagonist in the plays grouped under the name of Le cycle médéen. In chronological order it will be mentioned: the essay Le sexe et l’Effroi (1994), Médée (2011), containing fragments with highlighted poetic bias, and the narrative L’origine de la danse (2013). In all these pieces, the figure of our character appears through the generic hybridisation perceived in both literary and pictorial genres.The aim of this research is  to emphasize, from the reception studies, the emotions surrounding Medea’s violence that is specified in the binomial bios (life) and thánatos (death), pulsion and expulsion from the genres crossing embodied in the singularity of the same author.
Keywords: Medea; Reception; Quignard; Violence; Emotion; Hybridisation